PROSES FISIOTERAPI DAN PENINGKATAN PENGETAHUAN TENTANG FISIOTERAPI PADA LANSIA DI KAB. SIMALUNGUN - Isa Harpika Br. Ginting; Ruth Mala Livia Theola Lumbantoruan (Nusantara Hasana Journal, 2025)
This study aims to evaluate community service activities that integrate physiotherapy and knowledge enhancement on exercise therapy and functional activities for the elderly in Simalungun Regency. The study was conducted in Raya Kahean Village using two-way discussions, live demonstrations, and quantitative evaluation through pre- and post-tests. The results showed a significant increase in the elderly's understanding and functional abilities after participating in the intervention program during 2020. These findings indicate that an integrative physiotherapy approach, with a combination of education and practical exercises, effectively improves the quality of life of the elderly and can be used as a model for similar activities in other areas.